IDEOLOGI KEBANGSAAN, IDENTITAS POLITIK, DAN EKONOMI CALON PRESIDEN PRABOWO SUBIANTO DALAM PROGRAM BEST RESULT FAST 2024-2029 - Sabarudin, Didin; Purwadi (JURNAL KEBANGSAAN RI, 2023)
The 2024 Presidential Election has produced three pairs of presidential and vice presidential candidates, namely Anies Rasyid Baswedan-Muhaimin Iskandar, Ganjar Pranowo-Mahfud M.D, and Prabowo Subianto-Gibran Rakabuming Raka, each of whom is supported by a coalition of parliamentary political parties resulting from the 2019 election and non-parliamentary political parties. Prabowo Subianto-Gibran Rakabuming Raka was promoted and supported by the coalition of 7 parliamentary and non-parliamentary political parties with 261 seats equal to 45.39% proposing the vision and mission of ASTA GITA and the Best Results Fast program, which is the implementation of the national ideology based on Article 33 of the Constitution with the principles of kinship and identity politics based on popular democracy and economic identity with a middle way economic school. This study is to elaborate on Prabowo Subianto's understanding, commitment, thoughts, and actions as stated in his vision, mission, and programs. Explanatory descriptive methods with a qualitative approach and interpretive analysis in a biographical model are used to obtain meaning and connections between national ideology and multidimensional political and economic identities. The results of the study show that ideology, political identity, and economics are interrelated between the figure of the Presidential candidate and the political work of political party machines and community choices which strengthen the legitimacy of identity, or give rise to resistance to different identities as a rejection of various forms of domination and hegemony from social actors in society. Keywords: presidential candidate, ideology, identity, Prabowo Subianto, program